Hedda Gabler - Ibsen, Henrik,Meyer, Michael (Bloomsbury Publishing Plc, 1979)
The play was intended as a tragedy on the purposeless of life imposed on the women of his time, both by their upbringing and by the social conventions which limited their activitie When it was first produced it met with misunderstanding and abuse.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books